Inventory Model with Time-Dependent Holding cost under Inflation when Seller Credits to Order Quantity - Sharma, Rajendra (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this study an inventory model is developed under which the seller provides the retailer a permissible delay in payments, if the retailer orders a large quantity. In this paper we establish an inventory model for non deteriorating items and time dependent holding cost under inflation when seller offers permissible delay to the retailer, if the order quantity is greater than or equal to a predetermined quantity. We then obtain optimal solution for finding optimal order quantity, optimal replenishment time and optimal total relevant cost. Finally, numerical example is given to illustrate the theoretical results and made sensitive analysis of various parameters on the optimal solution.